Building a culture of peace at the University of Guayaquil: Mediation as a resource for improvement and change - Novel Martí, Gloria (Revista Universidad de Guayaquil, 2014)
Here we present the initiative that is being carried out at the University of Guayaquil (UG) for the insertion of the Mediation Services (SMUG). Its purpose is to support organizational change and improvement, managing also the conflicts that arise. In the next phase, the SMUG will offer services at the community and family unit. This work will allow that both professors and students at the UG learn about the availability of this resource: Mediation Services “SMUG”. We hope that this work will also motivate dialog, suggestions, and collaborative proposals at the individual and new networks
Keywords: Culture of Peace; Sumak kawsay; Good Living; prevention and conflict management; organizational improvement and change; conflict costs; community outreach; organizational mediation